THE USE OF SMARTPHONES AND APPS TO IMPROVE ENGLISH LEARNERS’ SKILLS IN THE CLASSROOM - Uzoqova , Xayriniso (Innovative Development in Educational Activities, 2023)
Nowadays. In this high-tech world technology is getting more advanced so that it impacts on every sphere of life including education, especially, learning and teaching English. Modern innovative technologies in the educational process increase the quality and effectiveness of education. In particular, there are several ways to use such information and communication technologies in learning and teaching a foreign language. Its advantages give important opportunity to make learning process more effective. The role of modern technology in language learning and teaching is immeasurable. It is famously used all over the world that technical devices such as IWB, Smart phones, Internet, Apps are able to grab everyone’s attention and respect since its great contribution in the achievement of learning and teaching language is limitless.